They call me No Sam! - Daywalt, Drew (Clarion Books, an imprint of HarperCollins Publishers, 2024)
"Meet Sam: an insolent pug -- and incidental hero -- who will stop at nothing to protect his family! When scientists Elaine and Gary Peterson adopt Sam to keep their son, Justin, company in the midst of a top-secret research project, they never imagine the precocious pup will cause more harm than good. But from chewing up Elaine's hair dryer (the "brain-melting heat cannon") to his inability to be house-trained (who could resist the 'pooping rug'?), the Petersons aren't sure how much more they can take. And that's before Sam starts harassing Justin's crush (and potential new friend), Phoebe, who Sam is sure is an evil wizard out to harm Justin. But when a pair of crooks encroaches on the Peterson household in an attempt to steal their confidential findings, Sam's actions -- never mind his reasoning for them -- just may save the day"--